Effects of COVID-19 on transportation services and travel behaviour in Malaysia - L Gungat; D R Deh; E E Putri (ResearchGate, 2023)
Movement restrictions implementation due the COVID-19 pandemic affected people's mobility and and transportation sectors globally. Tourism, retail, transportation, and hospitality also suffered significant consequences that indirectly impacted a country's economic stability. Hence, this paper presents the Malaysian experience with the effects of the pandemic on transportation services and travel behaviour. Online sources, secondary data and a questionnaire survey were employed to collect the relevant data. These data were further analysed and presented in this paper. In general, transportation sectors involving air, rail and public bus showed decreased demand and services. A severe drop in services was observed in air transportation which is more than 97%. Most people prefer not to use public transportation to avoid the risk of COVID-19 infection. Noticeable changes in travel behaviour and mode preference during and pre-pandemic are observed, particularly on trips related to work/school. Key pandemic factors concerning transportation were fear of infection and social distance. Hence, most people prefer to use a private vehicle. The changes in transportation service and travel behaviour result in severe losses in the transportation sector in Malaysia.